Assessing the use of Salt and Activated Carbon in the Cleaning of Biogas for Households in Mukono District - Magdalene D Atugabiire (Uganda Christian University, 2024)
This study investigates the effectiveness of salt and activated carbon in cleaning and purifying biogas. Biogas, a gas mixture produced from decomposing organic matter in an oxygen-deprived environment, contains 50–70% methane (CH₄) and 30–50% carbon dioxide (CO₂), along with traces of hydrogen sulphide (H₂S) and water vapor (H₂O). The presence of CO₂, H₂S, and water vapor can impact energy conversion device performance and flame combustion. Thus, their removal is critical for enhancing biogas quality. The study employed a chemical absorption method using an aqueous alkaline salt solution (NaOH) and activated carbon to cleanse and enrich biogas. The process involved scrubbing CO₂ and H₂S from biogas generated from household waste, faecal material, and cow dung. Additionally, activated carbon adsorbed water vapor as the gas passed through. The objectives included assessing different salt types for effective removal of hydrogen sulphide, carbon dioxide, and water vapor, ultimately promoting cost-effective biogas cleaning for household cooking.
Undergraduate Research